Induction of dormancy in Lobesia botrana by long day and high temperature conditions - Tzanakakis Μ. Ε.; Savopoulou-Soultani Μ.; Oustapassidis, C. S.; Verras, S.C.; Hatziemmanouel Η. (ENTOMOLOGIA HELLENICA, 1988)
Lobesia botrana (Denis and Schiffermueller) (Lepidoptera: Tortricidae) is known to enter a facultative autumnohibernal diapause-mediated dormancy in the pupal stage, when the embryonic and early larval stages are exposed to short-day photo-periods. Yet, in a laboratory stock originating from northern Greece and reared for years on an artificial larval diet, dormancy occurred also under a long-day photo-period. When the eggs were incubated at 30oC in the dark or at 26 oC under the natural daylength of August in northern Greece, and the larvae grew at L:D 16:8 and 25-26 oC, but not 20 oC, a substantial percentage of the pupae entered dormancy. This dormancy seems to be diapause-mediated. It is not known whether it is a typical summer diapause.